Representations of Violent Young Women - Chappell, Susannah (Operant Subjectivity, 1997)
This Q study investigated representations - portrayals of what a person is like - of young violent women. Its impetus was reporting in the press which was expressing concern about a rise in "acceptability of violence" among young women. The data obtained in the study refute this concern. While the one representation which portrayed a fictional character was of a woman who was frighteningly violet, the other four depicted women known to the participants whose Q sorts described the. All of these were quite "ordinary," their violence was minor, and it was not seen as a central feature of their character. These results suggest that there is something of a "moral panic" being created. Some of the reasons for this are discussed.